Aspectos científicos, tecnológicos e sociais na construção profissional docente - Fagundes, Suzana Margarete Kurzmann (2015)
Given the contemporary challenges related to aspects on science and technology, the teachers and future teachers face the need to build and/or develop knowledge about their profession, adapting their practice and constructing a vision in which its compromise as a teacher to be focused to the social dimension of those issues. Thus, was developed, implemented and evaluated an educational proposal along with the discipline of Biological Science Teaching I, in the first half of 2013, in the Federal University of Santa Maria/RS. In this proposal we introduced, initially, through diversified strategies/activities, issues that arise as a trend in the process of teaching practice, such as: Content Type, the Three Pedagogical Moments (3MP), the Thematic Approach and the CTS approach. Then, we presented the basic elements of an educational planning and as a teaching resource, a matrix, which is characterized to organize and systematize the scientific, technological and social contents about the topic/subject that someone want to work. This matrix allows, through many paths, the balanced choice of different aspects such as political, environmental and ethical, and not only the use of conceptual contents in didactic planning. was investigated thus a possible evolution on the part of future biology teachers, trying to identify them according to the level of ownership of didactic knowledge built during the semester and determined through analysis and checked a posteriori. Were identified, then three levels of ownership: Thematic Approach Traditionally, Thematic Approach Dialogic and Thematic Approach Critical.